2014
DOI: 10.1016/j.eururo.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Candidate Gene Association Studies of Lower Urinary Tract Symptoms in Men

Abstract: ContextAlthough family studies have shown that male lower urinary tract symptoms (LUTS) are highly heritable, no systematic review exists of genetic polymorphisms tested for association with LUTS.ObjectiveTo systematically review and meta-analyze studies assessing candidate polymorphisms/genes tested for an association with LUTS, and to assess the strength, consistency, and potential for bias among pooled associations.Evidence acquisitionA systematic search of the PubMed and HuGE databases as well as abstracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 97 publications
0
25
0
1
Order By: Relevance
“…The latter has been previously studied in many reports, but mainly via a candidate-gene approach. Cartwright et al [15] recently gathered the results of those multiple reports in a systematic review and performed meta-analyses. They concluded that only rs731236 variant of the vitamin D receptor gene was consistently associated with a reduced risk of LUTS in men across different populations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The latter has been previously studied in many reports, but mainly via a candidate-gene approach. Cartwright et al [15] recently gathered the results of those multiple reports in a systematic review and performed meta-analyses. They concluded that only rs731236 variant of the vitamin D receptor gene was consistently associated with a reduced risk of LUTS in men across different populations.…”
Section: Discussionmentioning
confidence: 97%
“…However, few studies have been conducted about genetic markers of BPH, and were mainly based on a candidate-gene approach. To date, no genetic variant has been clearly linked to BPH, BPE, or LUTS, except in vitamin D pathway [15]. In addition, a major limitation of previously published data is the lack of correct phenotype definition, the endpoint being loosely BPH, LUTS, prostate volume categories, or BPH treatments.…”
Section: Introductionmentioning
confidence: 93%
“…22 A meta-analysis provided moderate evidence of the genetic association for urinary symptoms in women, with certain genes having an odds ratio (OR) of 2.5 for OAB and 2.1 for SUI. 23 Although specific genetic predisposition has not been identified, a systematic review of genetic studies found that collagen type 3 alpha 1 was associated with POP (OR 4.79). 24 …”
Section: Phase I: Predisposing Factors For Pelvic Floor Disordersmentioning
confidence: 99%
“…None of these studies provided compelling evidence that one of these polymorphisms (or combinations thereof) could serve as a clinically relevant marker [4,5]. As indicated by Cartwright et al [5], many of these genetic studies are hampered by a small sample size, lack of genotyping quality control, inadequate adjustment for populations from heterogeneous descent groups, and poorly defined/inhomogeneous study endpoints.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Within the past decade numerous polymorphisms in the steroid-metabolism pathway, in cytokine genes, in the vitamin D receptor gene, the a-adrenoceptor gene, in homeobox genes, in the angiotensin converting enzyme, the glutathione S-transferase gene, and in the nitric oxide system (just to mention the most frequently studied ones) have been correlated to several clinical parameters of BPH/LUTS, such as symptom status, prostate volume, maximum urinary flow rate and the natural history of the disease [4,5]. None of these studies provided compelling evidence that one of these polymorphisms (or combinations thereof) could serve as a clinically relevant marker [4,5].…”
Section: Conflicts Of Interestmentioning
confidence: 99%